Robotics - Siciliano, Bruno; Sciavicco, Lorenzo; Villani, Luigi; Oriolo, Giuseppe (Springer, 2010)
In the last 25 years, the field of robotics has stimulated an increasing interest in a wide number of scholars, and thus literature has been conspicuous, both in terms of textbooks and monographs, and in terms of specialized journals dedicated to robotics. This strong interest is also to be attributed to the interdisciplinary character of robotics, which is a science having roots in different areas. Cybernetics, mechanics, controls, computers, bioengineering, electronics — to mention the most important ones — are all cultural domains which undoubtedly have boosted the development of this science. Despite robotics representing as yet a relatively young discipline, its foundations are to be considered well-assessed in the classical textbook literature. Among these, modelling, planning and control play a basic role, not only in the traditional context of industrial robotics, but also for the advanced scenarios of field and service robots, which have attracted an increasing interest from the research community in the last 15 years. This book is the natural evolution of the previous text Modelling and Control of Robot Manipulators by the first two co-authors, published in 1995, and in 2000 with its second edition. The cut of the original textbook has been confirmed with the educational goal of blending the fundamental and technological aspects with those advanced aspects, on a uniform track as regards a rigorous formalism. The fundamental and technological aspects are mainly concentrated in the first six chapters of the book and concern the theory of manipulator structures, including kinematics, statics and trajectory planning, and the technology of robot actuators, sensors and control units. The advanced aspects are dealt with in the subsequent six chapters and concern dynamics and motion control of robot manipulators, interaction with the environment using exteroceptive sensory data (force and vision), mobile robots and motion planning.
Modelling, Planning and Control